1999
DOI: 10.1002/cjce.5450770231
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of an internally circulating fluidized bed reactor for thermal treatment of industrial solid wastes

Abstract: A predictive mathematical model is developed to describe and characterize the key design variables of a novel Internal Circulating Fluidized Bed Combustor. The model is based on fundamental principles of heat transfer, mass transfer, hydrodynamics and reaction kinetics. Under justifiable assumptions unsteady state mathematical equations are written and solved. The input parameters of the model are gas and solid flowrates, solid circulation flux, as well as physical properties of gas and solids, The model allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…According to Hadzismajlovic et al, the particle velocity in the annulus section is uniform except in the conical section at the bottom of the ICFB. The flow of solid particles in the annular section was treated as a plug flow except in the conical section . Since the flow of solid particles in the annular section is not fluidized in our experiments, SRR could be calculated with Equation (1).…”
Section: Methodssupporting
confidence: 80%
“…According to Hadzismajlovic et al, the particle velocity in the annulus section is uniform except in the conical section at the bottom of the ICFB. The flow of solid particles in the annular section was treated as a plug flow except in the conical section . Since the flow of solid particles in the annular section is not fluidized in our experiments, SRR could be calculated with Equation (1).…”
Section: Methodssupporting
confidence: 80%
“…The ICFBs are widely applied as reactors in such processes as heterogeneous catalysis (Al-Mayman and Al-Zahrani 2003), gasification of biomass (Kersten et al 2003), coal and the pyrolysis of plastics (Aguado et al 2003). New possible areas of applications are desulfurization of flue gases and thermal utilization of wastes (Mukadi et al 1999). A basic disadvantage of an ICFB apparatus is related to the scale-up and development of an industrial unit.…”
mentioning
confidence: 99%
“…[2][3][4] In an ICFB, a draft tube is inserted into a fluidized bed dividing the bed into two regions. By fluidizing solids in the draft tube at a velocity ϳ5-10 times the minimum fluidizing velocity (U mf ) and the annulus at 0.7-1.5U mf , it is possible to induce a gross circulation of bed material up to the draft tube and down to the annulus region.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies on waste incineration in ICFB have been reported. 3,7,8 However, ICFB incineration study is relatively sparse compared with those in bubbling and circulating fluidized beds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation